O tempo da ironia em “The love song of J. Alfred Prufrock”, de T. S. Eliot - Aguiar, Angiuli Copetti de (2016)
The works of the English poet T. S. Eliot (1888-1965) reveal a thematic and aesthetic interest in the subject of “time” as human experience, whether collective, as history, or subjective, as memory. His first poem, “The Love Song of J. Alfred Prufrock” (1916), is a pioneer experiment on the stream of consciousness technique through which are shown the complex mental processes of its character, Prufrock, in a complex fabric of times and logical chains. The temporal dimension was an object of analysis for many critics of the poem, most of whom relied on interpretations based on philosophical perspectives, dispensing, however, with another fundamental aspect of “The Love Song”: the irony. Thus we sought to reconcile in our study the two main aspects of the poem, time and irony, lessening the philosophical perspective in favor of an aesthetic and stylistic approach. For this purpose we proposed an analysis of the time in “The Love Song”, based on the the rhetorical study of Dubois et. al. (1960), and its interpretation following the insights of Søren Kierkegaard (2010; 2013) and Paul de Man (1986; 1996) concerning the relationship between irony and temporality. As a result, we observed that the kind of time depicted in the poem corresponds to the time that theoriticians define as characteristic of the structure of irony: a time in which the present is felt as tedious or discontinuous; the past, as absent of mystified; and the future, as postponed or as anxiety.